EFFECT OF CADMIUM CHLORIDE ON THE OVARIAN ACTIVITY IN FRESH WATER CATFISH CLARIAS BATRACHUS (LINN.) - SAKSENA, D. N.; AGARWAL, ABHILASHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1986)
Effect of Cadmium chloride on the ovaries of Clarias battrachus (Linn) has been studied Treatment of 400 mg/l Cadmium chloride during September to November reduced the ovarian activity. Stage II (vitellogenic) oocytes and gonosomatic index (GSI) significantly decreased in treated fishes. The number of at retic follicles were increased due to Cadmium chloride after 45 days. Such an influence on ovarian regression may be attributed to the lowered level of gonadotropin release following the exposure to the heavy metal. After 90 days of treatment the GSI was decreased while at retic follicles were increased. It is concluded that after 45 days of treatment a process of recrudescence starts.